Juventude e acesso ao mercado de trabalho: a expectativa de futuro de estudantes e egressos do curso de Serviço Social do ICSEZ/UFAM - Nunes, Thais Azevedo (BRASIL, 2023)
Despite the advances that youth have been making, there are many challenges that surround them when it comes to public policies and access to the job market. The youth public is a recent target of debate within the public agenda, so it is essential to reflect on the concerns of youth, especially university students. In a current scenario of economic crisis, which has occurred since 2015 in Brazil and aggravated by the Covid-19 pandemic, the world of work is undergoing major transformations. Such changes affect young people more intensely, due to the lack of opportunities and imposed demands. In Parintins-Am, the drama of unemployment experienced by graduates brings up an uncertain reality for graduating students. Therefore, this monographic work is aimed at graduating students and graduates of the Icsez/Ufam Social Work course and aims to know the expectations they build in relation to insertion in the labor market and how, in fact, graduates experience this reality. To carry out this research, we used the qualitative and quantitative research as theoretical support, the techniques used for data collection were the application of the Survey Questionnaire on-line through Google Forms. The research results reveal that the current scenario of uncertainties, arising from the economic crisis, the lack of knowledge and the lack of income and work policies and programs directly affect the expectation of a professional future both for students and for newly graduated professionals in Parintins-AM . When comparing the data collected between graduating students and newly graduated professionals, we noticed that graduating students and graduates dream of working in the training area. However, the reality is different and complex, the graduates live their daily lives with the anguish of the lack of work in the city, which directly affects their expectations of the future.